2015
DOI: 10.1038/srep12925
|View full text |Cite
|
Sign up to set email alerts
|

N Doping to ZnO Nanorods for Photoelectrochemical Water Splitting under Visible Light: Engineered Impurity Distribution and Terraced Band Structure

Abstract: Solution-based ZnO nanorod arrays (NRAs) were modified with controlled N doping by an advanced ion implantation method, and were subsequently utilized as photoanodes for photoelectrochemical (PEC) water splitting under visible light irradiation. A gradient distribution of N dopants along the vertical direction of ZnO nanorods was realized. N doped ZnO NRAs displayed a markedly enhanced visible-light-driven PEC photocurrent density of ~160 μA/cm2 at 1.1 V vs. saturated calomel electrode (SCE), which was about 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(140 citation statements)
references
References 48 publications
5
133
0
2
Order By: Relevance
“…In ZnO Raman spectrum, peak at ∼438 cm −1 can be assigned to a nonpolar E2 (high) optical phonon mode that corresponds to the band characteristics of wurtzite hexagonal phase of ZnO. 28,29 The peak at ∼380 cm −1 is due to the A1 (TO) mode, whereas, peaks around 202 and 330 cm −1 are due to resonance conditions and can be assigned to acoustic phonon overtone and optical phonon overtone modes with A1 symmetry, respectively. 30 Moreover, the broad peak around 1145 cm −1 belongs to the Raman 2LO mode.…”
Section: Resultsmentioning
confidence: 99%
“…In ZnO Raman spectrum, peak at ∼438 cm −1 can be assigned to a nonpolar E2 (high) optical phonon mode that corresponds to the band characteristics of wurtzite hexagonal phase of ZnO. 28,29 The peak at ∼380 cm −1 is due to the A1 (TO) mode, whereas, peaks around 202 and 330 cm −1 are due to resonance conditions and can be assigned to acoustic phonon overtone and optical phonon overtone modes with A1 symmetry, respectively. 30 Moreover, the broad peak around 1145 cm −1 belongs to the Raman 2LO mode.…”
Section: Resultsmentioning
confidence: 99%
“…The valence band of TiO 2 and ZnO (mostly from O 2p orbitals) is quite deep, ≈1.6-1.7 V, more positive than the O 2 /H 2 O potential, while the conduction band (mainly from Ti 3d or Zn 3d) is only barely more negative than the H 2 O/H 2 potential. [142,220] However, the low solubility of these 2p and 3p anions in TiO 2 and ZnO as well as the unbalanced charges created from the replacement of O 2− by these anions (e.g., C 4− , N 3− ) and their associated recombination limits both optical absorption and charge collection efficiencies of materials. Typically, this could be done by doping TiO 2 and ZnO with some 2p or 3p anions with higher atomic p orbital energies than that of O, such as C, N, S, and P. [219] Hoang et al demonstrated that incorporating N into TiO 2 NW arrays by annealing TiO 2 NWs in NH 3 flow can lower the band gap of TiO 2 to ≈2.4 eV.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…Wang et al . studied solution‐based ZnO nanorod arrays modified by controlled N doping using an advanced ion‐implantation method . They subsequently utilized NW arrays as photoanodes for photoelectrochemical water splitting under visible‐light irradiation.…”
Section: Progress In Contemporary Researches Of Doped Zno Applicabilimentioning
confidence: 99%